When marital institutions break down: Impact and adaptation among the Enga of Papua New Guinea. (1st March 2021) - Wiessner, Polly; Pupu, Nitze
Abstract: Abstract: Institutions to regulate marriage and sexual mores are nearly universal across human societies to assure production and reproduction and weave the fabric of society. The stakeholders are many. What happens when marital traditions break down in times of rapid change? Taking a long-term perspective, we will first look at developments in marital institutions that occurred after the arrival of the sweet potato (ca. 400 BP) among the Enga of Papua New Guinea. Next, we will document changes in recent marital practices of 402 Enga women collected in 2007. With data from 270 public forums in customary courts applying restorative justice between 2008 and 2019, we will consider (a) the impact of the breakdown of marital institutions and (b) responses to adapt norms to new practices. In the absence of regulation by 'traditional' institutions, individuals pursue their own interests and passions with negative outcomes for families and communities. Communities, non-governmental organisations, churches and government throughout Papua New Guinea are seeking to adapt norms to new conditions. We consider both norm change resulting from community action via customary courts and what communities strive to preserve. Cultural institutions and accompanying norms are important factors in assuring production and reproduction; however, they can instill attitudes that inhibit adaptation.